Coach competence, justice, and authentic leadership: An athlete satisfaction model - Soto-García, D.; Reynoso-Sánchez, L. F.; García-Herrero, J. A.; Gómez-López, M.; Carcedo, R. J. (International Journal of Sports Science & Coaching, 2023)
This study analyzed the relationship between athletes' perception of coach competence and their satisfaction, mediated by the influence of authentic leadership and perceived justice in team sports players. A cross-sectional study carried out with 115 (49.6% women and 50.4% men; 17.96 ± 2.85 years old; 8.18 ± 4.67 years of experience), soccer (53.9%), and handball (46.1%) players, all members of performance teams. The player's perception of coach competency, authentic leadership, justice, and satisfaction with the coach was measured. Correlation between variables and comparison throughout gender, sport, and experience were analyzed. Also, a multiple sequential mediation model was tested (coach competence ? authentic leadership ? coach justice ? satisfaction with the coach, 95% CI 10,000 bootstrapping). There was a significant relationship (p < 0.05) between all the variables, differences in the perception of satisfaction with the coach based on sport, and the perception of coach justice related to the years of experience in the sport. The multiple sequential mediation model (d21 = 0.468; p < 0.001; IE = 0.098; CI = 0.020; 0.183), and the total indirect effect (IE = 0.310; CI = 0.138; 0.479) were significant. In conclusion, the results suggest that athletes emphasize that if the coach is competent and promotes justice to achieve the athlete's satisfaction without neglecting the influence of their authentic leadership style, this can strengthen their relationship and satisfaction with the coach.